Precision Molecular Threading/Dethreading. (8th June 2020) - Groppi, Jessica; Casimiro, Lorenzo; Canton, Martina; Corra, Stefano; Jafari‐Nasab, Mina; Tabacchi, Gloria; Cavallo, Luigi; Baroncini, Massimo; Silvi, Serena; Fois, Ettore; Credi, Alberto
Abstract: The general principles guiding the design of molecular machines based on interlocked structures are well known. Nonetheless, the identification of suitable molecular components for a precise tuning of the energetic parameters that determine the mechanical link is still challenging. Indeed, what are the reasons of the "all‐or‐nothing" effect, which turns a molecular "speed‐bump" into a stopper in pseudorotaxane‐based architectures? Here we investigate the threading and dethreading processes for a representative class of molecular components, based on symmetric dibenzylammonium axles and dibenzo[24]crown‐8 ether, with a joint experimental–computational strategy. From the analysis of quantitative data and an atomistic insight, we derive simple rules correlating the kinetic behaviour with the substitution pattern, and provide rational guidelines for the design of modules to be integrated in molecular switches and motors with sophisticated dynamic features. Abstract : Fine mechanics : A systematic experimental and computational study explains why tiny structural changes in the extremities of a molecular axle can allow or prevent its insertion in the cavity of a macrocycle. These results provide guidelines to design interlocked molecules with predetermined dynamic features, that can be used to make nanostructured machines, motors and materials.